European Neighbourhood Policy, A Polish Perspective - Marcinkowska, Paula (UNISCI Journal, 2016)
Before the bing-bang enlargement of the EU in 2004, the Union needed to define a coherent policy towards its new neighbours. The European Neighbourhood Policy was formulated when Poland became a member of the EU. Due to its close ties with the Eastern European countries, Poland tried to shape the EU foreign policy towards its neighbouring countries and became their advocate in Brussels. In 2009 it succeeded in establishing the Eastern Partnership as one of the dimensions of the European Neighbourhood Policy.